Experimental and Clinical Evaluation of Transperitoneal Laparoscopic Ureteronephrectomy in Dogs1. Issue 5 (1st February 2013) - Mayhew, Philipp D.; Mehler, Stephen J.; Mayhew, Kelli N.; Steffey, Michele A.; Culp, William T. N.
Abstract Objective To report a surgical technique for transperitoneal laparoscopic ureteronephrectomy (TLU) in dogs and describe complications and outcome in a cohort of dogs. Study Design Experimental study and case series. Animals Purpose‐bred research dogs (n = 3) and canine clinical cases (9). Methods In 11 of 12 dogs, a 3 port laparoscopic approach was used and in 1 dog a 4‐port approach was used. Incision through the retroperitoneal space was followed by early dissection of the ureter to aid retraction and elevation of the renal hilus. Dissection was performed principally by use of a vessel‐sealing device. Ligation of the renal hilar vessels was accomplished using laparoscopic hemoclips. Experimental dogs were euthanatized and necropsied. Results In 3 experimental dogs, no intraoperative complications occurred and conversion to an open approach was unnecessary. Of 9 clinical cases, conversion to an open approach was required in 2 dogs, because of severe hydroureter obscuring observation in 1, and uncontrollable retroperitoneal hemorrhage in the other dog. In 1 dog hemorrhage from the renal capsule and renal vein was controlled laparoscopically. No other major complications occurred. All dogs were discharged. Conclusions Transperitoneal laparoscopic ureteronephrectomy is feasible in dogs although conversion to an open approach should be considered when uncontrollable hemorrhage is encountered or the view is obscured by anatomic alteration.